1997
DOI: 10.1111/j.1479-828x.1997.tb02225.x
|View full text |Cite
|
Sign up to set email alerts
|

Candida G lab rata Chorioamnionitis Following In Vitro Fertilization and Embryo Transfer

Abstract: Candida glabrata is a yeast which is considered to be a commensal of the vagina with limited pathogenicity in the immunocompetent host. We report 2 cases of severe chorioamnionitis occurring in pregnancies achieved by in vitro fertilization techniques which resulted in preterm delivery and pregnancy loss. Candida glabrata as the causative agent was probably introduced into the uterus by the cannula at the time of embryo transfer. It is recommended that appropriate investigation of the microbial flora of the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 9 publications
0
14
0
1
Order By: Relevance
“…glabrata infection has also been reported as a cause of chorioamnionitis in healthy pregnant women [6][7][8]. The majority of cases appear to be reported in the IVF population and present at 15-24 weeks gestation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…glabrata infection has also been reported as a cause of chorioamnionitis in healthy pregnant women [6][7][8]. The majority of cases appear to be reported in the IVF population and present at 15-24 weeks gestation.…”
Section: Discussionmentioning
confidence: 98%
“…The majority of cases appear to be reported in the IVF population and present at 15-24 weeks gestation. The authors propose that the possible source of infection is the lower genital tract, with introduction of organisms into the uterus at time of embryo transfer [6][7][8]. In the non-IVF population, C. glabrata chorioamnionitis has been associated with foreign bodies (cerclage and intrauterine devices) and immunosuppression (untreated gestational diabetes) [6].…”
Section: Discussionmentioning
confidence: 99%
“…Heretofore, little information was available to guide providers. Sfameni et al (4) reported two cases of C. glabrata causing chorioamnionitis within the setting of IVF. With the first case, the investigators reported their experience with a subsequent embryo transfer.…”
Section: Discussionmentioning
confidence: 98%
“…Nous avons retrouvé 12 cas publiés de chorioamniotite à C. glabrata en effectuant une recherche sur Pubmed avec les mots clés Candida glabrata et pregnancy (Tableau 1) [6][7][8][9][10][11][12][13][14]. Sept cas sont survenus à la suite d'une FIV [6][7][8]11] (Tableau 1). Si les facteurs de risques décrits semblent classiques en dehors des cas avec FIV (cerclage, diabète non traité, drépanocytose, ventilation maternelle et cathéter central), les cas décrits sur des FIV sont le plus souvent isolés associés dans trois cas à des ruptures des membranes dont il est difficile de distinguer s'il s'agit d'un facteur de risque ou d'un symptôme de la chorioamniotite à bas bruit.…”
Section: Discussionunclassified